2022
DOI: 10.3390/foods11223555
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Traditional Chinese Sesame Oil by Using Headspace Solid-Phase Microextraction/Gas Chromatography–Mass Spectrometry, Electronic Nose, Sensory Evaluation, and RapidOxy

Abstract: Xiao Mo Xiang You (XMXY) is a traditional Chinese sesame oil variety that is obtained through a hot water flotation process. This unique process gives the oil a unique aroma, health benefits, and excellent product stability. Although XMXY is always the most expensive among all the sesame oil varieties, it is usually used as a flavoring in many traditional Chinese daily food products and is increasingly popular. In order to reveal the characteristics of the oil, the volatile components, sensory evaluation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 47 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…The aromatic quality of sesame oil is mainly attributed to volatile compounds, including pyrazines, furans, thiazoles, pyrroles, alcohols, and aldehydes [3,6]. Specifically, methanethiol, dimethyl disulfide, methyl-pyrazine, 2-ethyl-6-methyl-pyrazine, 3-ethyl-2, 5-dimethyl-pyrazine, 2furan methanol, etc., play important roles in the flavor of sesame oil [7]. Meanwhile, as reported, pyrazine and other substances might be the main ingredients of sesame oil essence [8].…”
Section: Introductionmentioning
confidence: 87%
“…The aromatic quality of sesame oil is mainly attributed to volatile compounds, including pyrazines, furans, thiazoles, pyrroles, alcohols, and aldehydes [3,6]. Specifically, methanethiol, dimethyl disulfide, methyl-pyrazine, 2-ethyl-6-methyl-pyrazine, 3-ethyl-2, 5-dimethyl-pyrazine, 2furan methanol, etc., play important roles in the flavor of sesame oil [7]. Meanwhile, as reported, pyrazine and other substances might be the main ingredients of sesame oil essence [8].…”
Section: Introductionmentioning
confidence: 87%
“…Samples were given to trained panelists ranging from the age of 25 to 44 to assess the quality of 'A4 and 'Beaumont'kernels in terms of their texture, colour and taste [13,26,39]. The trained panelists employed in this study were 5 males and 5 females as described by similar studies where the panelists ranged between 7 and 12 in number [40][41][42]. Moreover, according to [13,39] with some minor modifications, the texture, colour, and taste of the kernels were evaluated using a 5-point scale as follows:Texture, where 1 denotes very hard, 2: hard, 3: slightly crispy, 4: crispy, and 5: very crispy; Colour, where 1 denotes very light, 2: light, 3: slightly brown, 4: brown, and 5: extremely brown and; Taste, where 1 denotes very nutty, 2: nutty, 3: slightly bitter, 4: bitter, and 5: extremely bitter.…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…Flavor is one of the typical characteristics of vegetable oil, which is an important index to judge the quality of vegetable oil as well. The volatile compounds of oil are the basic substances of flavor generation, and their formation is closely related to the preparation technology (Chen et al., 2022). It is reported that roasting before pressing can render oil with some unique flavors, such as nutty, almond, and caramel aromas (Sun et al., 2022).…”
Section: Introductionmentioning
confidence: 99%